Update of the Scientific Opinion on the risks for human health related to the presence of perchlorate in food - EFSA Panel on Contaminants in the Food Chain (CONTAM); Helle Katrine Knutsen; Agneta Åkesson; Vasileios Bampidis; Margherita Bignami; Laurent Bodin; Gisela Degen; Antonio Hernández‐Jerez; Tim Hofer; Christer Hogstrand; Stefano Landi; Jean‐Charles Leblanc; et al. (EFSA Journal)
Abstract The European Commission asked EFSA to update its 2014 risk assessment on perchlorate in food. Perchlorate is a contaminant of both natural and anthropogenic sources present in food and drinking water. It is a substrate for the sodium iodide symporter (NIS) and competitively inhibits the uptake of iodide into the thyroid. Experimental animal studies show that perchlorate exposure during pregnancy can result in neurodevelopmental toxicity. The CONTAM Panel established a tolerable daily intake of 1.4 μg/kg body weight per day, based on the inhibition of thyroid iodine uptake in healthy adults. The tolerable daily intake (TDI) takes into account the sensitivity of the fetus to maternal thyroid hormone disturbance and uncertainty around the impact of iodine deficiency on the effects of perchlorate during fetal development. This TDI is applicable for both a short‐term (approximately 2‐week period) and chronic exposures based on the mode of action of perchlorate, its toxicokinetic properties and the key study used to derive the TDI. An acute reference dose (ARfD) was not deemed necessary. EFSA received a total of 40,356 analytical results, between 2016 and 2022, which were considered for the dietary exposure assessments. A chronic dietary exposure assessment for all age groups and a short‐term dietary exposure assessment for pregnant women were calculated. The CONTAM Panel concluded that chronic and short‐term dietary exposure estimates to perchlorate were below the TDI for all age groups including pregnant women, with the exception at the upper bound of the P95 for infants, breastfed infants and formula‐fed infants. Even if the limitations in analytical methods, leading to a large difference between lower bound (LB) and upper bound (UB) dietary exposure, reduces the certainty in this conclusion for infants, breastfed infants and formula‐fed infants, the uncertainty analysis indicates a higher (above 50%) likelihood of ‘no concern’ for all scenarios.